Kingdom of the Netherlands-Netherlands : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2006)
This paper investigates the determinants of trend growth and total factor productivity (TFP) growth in the Netherlands, and underscores the importance of boosting structural reforms in the Netherlands. It examines the fiscal incentives and tax deductibility. The paper summarizes recent developments in the housing market in the country. It provides systematic empirical evidence on a key measure of volatility in different sources of tax revenues. It examines the role of business cycle fluctuations, the impact of the Dutch pension fund system, corporate location decisions, and other specific factors.